1995
DOI: 10.1111/j.1477-9552.1995.tb00748.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Minimum Wages on Uk Agriculture

Abstract: agriculture isthe only sector in the UK economy covered by any form of minimum wage legislation. However, the recent denunciation of an ILO convention covering minimum wages in agriculture has paved the way for the abolition of the Agricultural Wages Boards. This paper investigates the impact of the system of minimum wages on the level and structure of earnings and employment in agriculture. On wages, our main conclusion is that the minimum wages set by the Agricultural Wages Boards are important determinants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…However, in the "new minimum wage research", minimum wages are not always harmful to employment (Bazen, 2000;Neumark and Wascher, 2007). The effect of minimum wages is negligible if minimum wages are close to competitive wages or the elasticity of labor demand is less sensitive to wages (Dickens et al, 1995, and1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the "new minimum wage research", minimum wages are not always harmful to employment (Bazen, 2000;Neumark and Wascher, 2007). The effect of minimum wages is negligible if minimum wages are close to competitive wages or the elasticity of labor demand is less sensitive to wages (Dickens et al, 1995, and1999).…”
Section: Introductionmentioning
confidence: 99%
“…Thus the AWB has been reactive in the sense that it has followed the level of average earnings in setting the minimum wage. If the objective of the AWB is solely to affect average earnings, the case for abolishing it is persuasive, particularly as Dickins et al (1995) found no statistically significant effect of minimum wages on employment. However, that earnings causality to run in the opposite direction, from minimum wages to earnings, it may be expected a priori that the elasticity is unity.…”
Section: Discussionmentioning
confidence: 99%
“…435 a simultaneous supply and demand model of the agricultural labour market for 1960-80, conclude that '... changes in the real prescribed wage have been largely ... offset by changes in the real premium, leaving real average earnings largely unaffected ' (p. 34). In contrast, Dickins et al (1995) examine the impact of minimum wages on the level and structure of both earnings and employment. They conclude that for the period 1954-91, '... a 10 percent increase in the minimum wage raises average earnings by around 4-5 percent ... [Therefore] removal of the minimum [wage] would almost certainly result in falling real wages'.…”
mentioning
confidence: 99%
“…However, in the ‘new minimum wage research’, there is no consensus on the direction of the effect of the minimum wage on employment (Bazen, ; Lemos, ; Neumark and Wascher, ). In economic theory, the minimum wage can have negligible effects on employment if the minimum wage is close to the competitive wage, or employers have bargaining power so that the elasticity of labour demand is less sensitive to labour cost (Dickens et al ., , ). In the monopsony model, the increased minimum wage can lead to an increase in employment.…”
Section: Introductionmentioning
confidence: 99%